Hospital pedagogy: the pedagogical performance at hospital environments (Research, Society and Development, 2017)
This study presents a working area of pedagogical performance, the Hospital Pedagogy, a Special Education modality, which has as intention the educational attendance to hospitalized children and adolescents, ensuring that they have their right to education guaranteed. This study aims to know the teaching work at hospital environments where, through different activities, it is ensured not only education but also the standard of living of its target audience. The general aim of this study was to increase our knowledge about Hospital Pedagogy as a playing field to the educator. The used methodology was the bibliographic review. In this study we discussed the history of Hospital Pedagogy in Brazil, which had its deployment in 1950s, but the recognition of the pedagogical work in this learning modality happened only in 2002, through the Ministry of Education. Concerning the attention modalities approached, they were: hospital educational attending and home educational attending. It was observed that the educator should work together with the health professionals with the intention to contribute to the integral development of the student and to his standard living, taking into account the multi/inter/transdisciplinary reality, that is, activities that integrate multiple sciences must be done, always having a social role making the learner understand the context in which he is placed so that he can overcome his limits. We consider relevant to highlight that, through the educator performance at hospital environments together with the medical team and the school in which the learner is regularly registered, it should be established appropriate activities that focus on achieving the whole development of the student, as well as guaranteed his access to education.